2000
DOI: 10.1081/pdt-100100556
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Solubility and Oral Bioavailability of Rutin by Complexation with 2-Hydroxypropyl-β-cyclodextrin

Abstract: The object of this study was to enhance the solubility, dissolution rate, and oral bioavailability of rutin by complexation with 2-hydroxypropyl-beta-cyclodextrin (HP-beta-CyD). The interaction of rutin with cyclodextrins (CyDs) was evaluated by the solubility, and ultraviolet (UV) and circular dichroism (CD) spectrophotometries. The chemical and enzymatic stability of rutin was examined in an alkaline buffer solution and in rat small intestinal homogenates, respectively. Dissolution rates of rutin and its CyD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
51
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(54 citation statements)
references
References 18 publications
2
51
0
1
Order By: Relevance
“…Hence, the results showed that the prepared apigenin-hydroxypropyl-β-cyclodextrin inclusion complex serves as a potential approach for new oral therapeutic agent formulation. 19 Miyake et al 39 improved solubility, dissolution rate, and oral bioavailability of rutin by complexation with 2-hydroxypropyl-β-cyclodextrin. The in vivo absorption study revealed that hydroxypropyl-β-cyclodextrin increased the oral bioavailability of rutin from the gastrointestinal tracts due to increase in solubility, faster dissolution rate, and gastrointestinal stability.…”
Section: Figure 1 Depicts the Guest-host Inclusion Complexes Formationmentioning
confidence: 99%
“…Hence, the results showed that the prepared apigenin-hydroxypropyl-β-cyclodextrin inclusion complex serves as a potential approach for new oral therapeutic agent formulation. 19 Miyake et al 39 improved solubility, dissolution rate, and oral bioavailability of rutin by complexation with 2-hydroxypropyl-β-cyclodextrin. The in vivo absorption study revealed that hydroxypropyl-β-cyclodextrin increased the oral bioavailability of rutin from the gastrointestinal tracts due to increase in solubility, faster dissolution rate, and gastrointestinal stability.…”
Section: Figure 1 Depicts the Guest-host Inclusion Complexes Formationmentioning
confidence: 99%
“…In these drugs, dissolution of the drug is the rate limiting step in the absorption process. To triumph over these obstacles, numbers of formulation approaches are reported including the use of surfactants (Allaboun et al, 2003;Balakrishnan et al, 2004;Chakraborty et al, 2009), lipids (Yeap et al, 2013), permeation enhancers (Burcin et al, 2010;Beg et al, 2011), formation of salt (Li et al, 2005;Serajuddin, 2007), co-crystallization (Shan & Zaworotko, 2008;Qiao et al, 2011;Chadha et al, 2012), solid dispersions (Serajuddin, 1999), inclusion complexes with cyclodextrins and modified cyclodextrins (Miyake et al, 2000;Veiga et al, 2000;Wang et al, 2000;Bannwart et al, 2001;Carrier et al, 2007;Gamsiz et al, 2010a,b;Gamsiz et al, 2011;Badr-Eldin et al, 2008;Kumar et al, 2013), nanosuspensions (Patravale et al, 2004), and colloidal vesicles like liposomes (Nazzal et al, 2002a;Manconi et al, 2013;Yang et al, 2013), and niosomes (Khazaeli et al, 2007;Bayindir & Yuksel, 2010;SezginBayindir et al, 2013;Jin et al, 2013) In modern years, self-nanoemulsifying drug delivery systems (SNEDDS) are the most popular and commercially feasible lipid-based formulation approach for improving oral bioavailability of poorly water soluble and lipophilic drugs (Pouton, 2006;Date, 2007;Shweta et al, 2011). SNEDDS are precisely defined as an isotropic multi-component drug delivery systems composed of a synthetic or natural oil, surfactant, and co-surfactant that have a unique ability of forming fine oil in water micro-or nano-emulsion upon mild agitation followed by dilutio...…”
Section: Introductionmentioning
confidence: 99%
“…Various strategies have been used to overcome the problems associated with oral absorption and bioavailability issues of poorly soluble drugs, such as particle size reduction (Aungst, 1993), complexation with cyclodextrins (Miyake et al, 2000), salt formation, solid dispersions (Sinha et al, 2010), use of surfactant, nanoparticles, nanocarriers (Bali et al, 2011), Nanoemulsions , self-emulsifying drug delivery system , prodrug formation, etc. Approaches used in past to improve the dissolution and bioavailability of NRG include complexation with b-cyclodextrin (Tommasini et al, 2004), phospholipid complexes (Semalty et al, 2010), solid dispersion with PVP (Kanaze et al, 2006), etc.…”
Section: Introductionmentioning
confidence: 99%